Connection between quantum-many-body scars and the Affleck–Kennedy–Lieb–Tasaki model from the viewpoint of embedded Hamiltonians. (28th August 2019) - Shiraishi, Naoto
Abstract: We elucidate the deep connection between the PXP model, which is a standard model of quantum many-body scars, and the Affleck–Kennedy–Lieb–Tasaki (AKLT) Hamiltonian. Using the framework of embedded Hamiltonians, we establish the connection between the PXP Hamiltonian and the AKLT Hamiltonian, which clarifies the reason why the PXP Hamiltonian has nonthermal energy eigenstates similar to the AKLT state. Through this analysis, we find that the presence of such nonthermal energy eigenstates reflects the symmetry in the AKLT Hamiltonian.